Mental health and work: a European perspective - Angelo Fioritti; Hlynur Jònasson; Lars de Winter; Chantal Van Audenhove; Jaap van Weeghel (Cambridge University Press, 2024)
Among the many social determinants of health and mental health, employment and work are getting momentum in the European political agenda. On 30-31 January 2024, a 'High-level Conference on Mental Health and Work' was held in Brussels on the initiative of the rotating Belgian Presidency of the European Union. It addressed the issue developing two different perspectives: (1) preventing the onset of poor mental health conditions or of physical and mental disorders linked to working conditions (primary prevention); (2) create an inclusive labour market that welcomes and supports all disadvantaged categories who are at high risk of exclusion (secondary and tertiary prevention). In the latter perspective, the Authors were involved in a session focused on 'returning to work' for people with mental disorders and other psychosocial disadvantages, with particular reference to Individual Placement and Support as a priority intervention already implemented in various European nations. The themes of the Brussels Conference will be further developed during the next European Union legislature, with the aim of approving in 4-5 years a binding directive for member states on Mental Health and Work, as it is considered a crucial issue for economic growth, social cohesion and overall stability of the European way of life.